Numerical Modelling of Displacement Pile Resistance in Sand Ground. Part 2: Discrete Model, at Rest Stage, Load Test - Vaidas Martinkus; Arnoldas Norkus; Džigita Nagrockienė (The Baltic Journal of Road and Bridge Engineering)
The article presents a continuation of research results on numerical modelling of displacement pile prototype ground (sand) resistance. Numerical modelling of ground resistance consists of three stages: restitution of initial soil stress state, the restoration of stress state developed during pile installation and the modelling of pile resistance against applied load (pile load test). Restitution of initial ground state induced in artificially created sand deposit after compaction procedures was realized by creating stress history and defining experimentally determined over consolidation stresses. Installation effects were restored using a well-known empirical approach based on relation between CPT test data and radial stress increase. Hardening soil model and its parameters were employed for modelling pile test substantiated in the first paper (Part 1) of the research. The discrete model of pile, soil layers, and pile-soil contact was created. Modelling of pile loading-unloading resistance was applied using an incremental loading procedure. Numerical analysis results validated with displacement pile prototype testing results.